Associations of DASH Diet in Pregnancy With Blood Pressure Patterns, Placental Hemodynamics, and Gestational Hypertensive Disorders - Wiertsema, Clarissa J. (J Am Heart Assoc, 2020)
BACKGROUND: The Dietary Approaches to Stop Hypertension (DASH) diet improves blood pressure in nonpregnant populations. We hypothesized that adherence to the DASH diet during pregnancy improves hemodynamic adaptations, leading to a lower risk of gestational hypertensive disorders. METHODS AND RESULTS: We examined whether the DASH diet score was associated with blood pressure, placental hemodynamics, and gestational hypertensive disorders in a population‐based cohort study among 3414 Dutch women. We assessed DASH score using food‐frequency questionnaires. We measured blood pressure in early‐, mid‐, and late pregnancy (medians, 95% range: 12.9 [9.8–17.9], 20.4 [16.6–23.2], 30.2 [28.6–32.6] weeks gestation, respectively), and placental hemodynamics in mid‐ and late pregnancy (medians, 95% range: 20.5 [18.7–23.1], 30.4 [28.5–32.8] weeks gestation, respectively). Information on gestational hypertensive disorders was obtained from medical records. Lower DASH score quartiles were associated with a higher mid pregnancy diastolic blood pressure, compared with the highest quartile (P<0.05). No associations were present for early‐ and late pregnancy diastolic blood pressure and systolic blood pressure throughout pregnancy. Compared with the highest DASH score quartile, the lower DASH score quartiles were associated with a higher mid‐ and late pregnancy umbilical artery pulsatility index (P≤0.05) but not with uterine artery resistance index. No associations with gestational hypertensive disorders were present. CONCLUSIONS: A higher DASH diet score is associated with lower mid pregnancy diastolic blood pressure and mid‐ and late pregnancy fetoplacental vascular function but not with uteroplacental vascular function or gestational hypertensive disorders within a low‐risk population. Further studies need to assess whether the effects of the DASH diet on gestational hemodynamic adaptations are more pronounced among higher‐risk populations.